Analysis of CPS (Country Partnership Strategy) Conformity to Vietnam of Korean ODA Projects - et al., Young-Chool Choi (International Journal of Advanced Science and Technology, 2020)
This study was conducted in recognition of a problem, namely that ODA (Official Development Assistance) projects organised by the donor country, and the detailed Country Partnership Strategy (CPS) targets established for the recipient country, were not in good agreement. The underpinnings of this study are as follows. First, the problem with Korea’s CPS for Vietnam is that its performance objectives are too abstractly presented, and therefore not enough to serve as a guideline. Second, some of Korea’s CPS targets for Vietnam (e.g. the transportation target) are not supported by any project. This may be said to be a problem, whether the initial creation of the CPS was wrong or insufficient review was made when deciding on aid projects for Vietnam. Third, among the CPS targets for Vietnam, the inclusiveness target (vulnerable class and social integration support) is supported by the largest number of projects, so the match between the project and the target is the strongest. Overall, since the Korean CPS for Vietnam is abstract, it is necessary to determine which projects have low consistency by applying methods such as social network analysis to increase the consistency of individual projects. In order to solve these problems, we believe that social network analysis methods can be efficacious.